2004
DOI: 10.1016/j.chembiol.2004.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Amphidinolide H, a Potent Cytotoxic Macrolide, Covalently Binds on Actin Subdomain 4 and Stabilizes Actin Filament

Abstract: The actin-targeting toxins have not only proven to be invaluable tools in studies of actin cytoskeleton structure and function but they also served as a foundation for a new class of anticancer drugs. Here, we describe that amphidinolide H (AmpH) targets actin cytoskeleton. AmpH induced multinucleated cells by disrupting actin organization in the cells, and the hyperpolymerization of purified actin into filaments of apparently normal morphology in vitro. AmpH covalently binds on actin, and the AmpH binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 46 publications
5
73
0
Order By: Relevance
“…MALDI-TOF mass analysis and the halo assay using the yeast harboring site-directed mutagenized actin revealed that the covalent binding of amphidinolide H (8) of small actin patches, followed by F-actin rearrangement into aggregates via the retraction actin fibers. These results indicated that amphidinolide H (8) is a novel F-actin stabilizer that covalently binds on actin [45].…”
Section: Mechanism Of Action Of Amphidinolides B and Hmentioning
confidence: 83%
See 2 more Smart Citations
“…MALDI-TOF mass analysis and the halo assay using the yeast harboring site-directed mutagenized actin revealed that the covalent binding of amphidinolide H (8) of small actin patches, followed by F-actin rearrangement into aggregates via the retraction actin fibers. These results indicated that amphidinolide H (8) is a novel F-actin stabilizer that covalently binds on actin [45].…”
Section: Mechanism Of Action Of Amphidinolides B and Hmentioning
confidence: 83%
“…These results suggest that amphidinolide B (2) enhances an interaction of actin and myosin directly and increases Ca 2ϩ sensitivity of the contractile apparatus mediated through troponin-tropomyosin system, resulting in an increase in the ATPase activity of actomyosin and thus enhances the contractile response of myofilament [44]. The molecular target of amphidinolide H (8) [25,26] has been investigated as follows [45,46]. The analysis of phenotypes of amphidinolide H-treated cells suggested that amphidinolide H (8) disrupt the actin organization in the cells, and the polymerization/depolymerization assay using purified actin indicated that amphidinolide H (8) stimulated actin polymerization and stabilized F-actin.…”
Section: Mechanism Of Action Of Amphidinolides B and Hmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cultured mammalian cells, both cause actin filament aggregation (Hoehn et al 1973;Usui et al 2004). In this study, we report the purification of Cuc E from A. macrocarpa and evaluated direct interaction between Cuc E and purified actin.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly it not only enhances phalloidin-binding to F-actin, but also binds to both F-and G-actins with similar affinities of 0.21 μM and 0.43 μM, respectively (Saito et al 2004). Amphidinolide H covalently binds to Tyr-198 of the actin monomer (Usui et al 2004). Tyr-198 is in subdomain IV, which faces toward the phalloidin-binding gap (Oda et al 2005).…”
Section: Marine Toxins That Stabilize Actin Filamentsmentioning
confidence: 99%